Efektivitas Penugasan Jurnal Harian Siswa dalam Meningkatkan Kualitas Keterampilan Menulis Siswa Sekolah Dasar - Cerillia Nanda Ocktaviani; Delly Puspita Anjami; Adrias Adrias; Fadila Suciana (Jurnal Pendidikan, Bahasa dan Budaya, 2025)
This research aims to analyze the effectiveness of daily journal assignments in improving elementary school students' writing skills. By using qualitative research methods through a library research approach, various literature and previous research results were studied comprehensively. The research results show that daily journal assignments have a significant positive impact on improving students' writing skills, which include linguistic aspects, idea development, writing coherence, and self-expression. This research also identified several supporting factors for the successful implementation of daily journals, such as consistency of assignments, clear guidelines, quality feedback, and support from the learning environment. The findings of this research provide practical implications for educators in developing effective writing learning strategies at the elementary school level.